2018
DOI: 10.1007/s11128-018-1844-7
|View full text |Cite
|
Sign up to set email alerts
|

Vertices cannot be hidden from quantum spatial search for almost all random graphs

Abstract: In this paper, we show that all nodes can be found optimally for almost all random Erdős-Rényi G(n, p) graphs using continuous-time quantum spatial search procedure. This works for both adjacency and Laplacian matrices, though under different conditions. The first one requires p = ω(log 8 (n)/n), while the second requires p ≥ (1+ε) log(n)/n, where ε > 0. The proof was made by analyzing the convergence of eigenvectors corresponding to outlying eigenvalues in the · ∞ norm. At the same time for p < (1 − ε) log(n)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…II, we prove that all Kronecker graphs generated by such regular, dominant-eigenvalue initiators asymptotically support optimal quantum search, reaching a success probability of 1 at time π √ N /2, and we give the critical jumping rate γ c that enables this. We prove this using properties of Kronecker products, a Lemma by Chakraborty et al [25], and an extension by Glos et al [26]. This general result proves Wong et al's conjecture with the complete initiator [9] as a special case.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…II, we prove that all Kronecker graphs generated by such regular, dominant-eigenvalue initiators asymptotically support optimal quantum search, reaching a success probability of 1 at time π √ N /2, and we give the critical jumping rate γ c that enables this. We prove this using properties of Kronecker products, a Lemma by Chakraborty et al [25], and an extension by Glos et al [26]. This general result proves Wong et al's conjecture with the complete initiator [9] as a special case.…”
Section: Introductionsupporting
confidence: 63%
“…Recall from the Lemma that c is an upper bound on the magnitudes of the non-principal eigenvalues of H 1 . Glos et al [26] noted that the supplemental material of [25] gives an explicit bound on r between −c/(1 + c) and c/(1 − c), inclusive.…”
Section: Dominant Eigenvalue Initiatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many other graph topologies have been considered. For instance, the algorithm has been investigated on complete bipartite graphs [5], on balanced trees [6], on Erdös-Rényi graphs [7,8], on the simplex of the complete graph [9] and on graphs with fractal dimensions [10,11]. Moreover, it has been shown that high connectivity and global symmetry of the graph are not necessary for fast quantum search [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Such problems involve running quantum algorithms for finding a marked node, known as quantum spatial search, in reverse. In fact, it has already been established that the problem of spatial search by quantum walk is optimal for G(n, p) [27][28][29]. Asymptotic dynamics of coined quantum walks on percolation graphs has been studied [30] while quantum dynamics on complex networks has also been numerically investigated [31][32][33].…”
mentioning
confidence: 99%